2023
DOI: 10.1111/jpm.12910
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of family caregivers in forensic mental health care—A qualitative evidence synthesis

Abstract: Accessible Summary What is known on the subject Internationally, research and policy agendas recommend that family caregivers of service users in mental health care be involved in care and treatment, to support the service user's recovery process. Family caregivers of service users in mental health care are often highly burdened. There is a lack of research‐based knowledge about the experiences of family caregivers of service users in forensic mental health care (FMHC) and their involvement in care and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…In that regard, the literature has reported that, for family caregivers, certain care settings (i.e., hospitals) are identified as contexts in which collaborative and trusting relationships with healthcare professionals are difficult to establish ( Dirik et al, 2017 ; Doody et al, 2017 ). The challenges for the involvement of family caregivers in care planning and decision-making have been discussed in empirical studies and literature reviews, with family caregivers’ voices being frequently critical of the lack of opportunities for active and meaningful involvement ( Stuart et al, 2020 ; Vestphal et al, 2023 ; Wilkinson & McAndrew, 2008 ). Gaps have also been identified between caregivers’ and clinicians’ views on the involvement of family ( Sharon et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In that regard, the literature has reported that, for family caregivers, certain care settings (i.e., hospitals) are identified as contexts in which collaborative and trusting relationships with healthcare professionals are difficult to establish ( Dirik et al, 2017 ; Doody et al, 2017 ). The challenges for the involvement of family caregivers in care planning and decision-making have been discussed in empirical studies and literature reviews, with family caregivers’ voices being frequently critical of the lack of opportunities for active and meaningful involvement ( Stuart et al, 2020 ; Vestphal et al, 2023 ; Wilkinson & McAndrew, 2008 ). Gaps have also been identified between caregivers’ and clinicians’ views on the involvement of family ( Sharon et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…[8,9] The expectations, confidence, pain management challenges, and problems of family caregivers were tried in various studies. [5,[10][11][12] To deliver patient-and family-centred care within palliative care services, it is crucial to thoroughly evaluate the needs and anticipations of family caregivers. [13] This study aims to better understand the feelings of caregivers behind their behaviors.…”
Section: Introductionmentioning
confidence: 99%